Lycoris species identification and infrageneric relationship investigation via graphene enhanced electrochemical fingerprinting of pollen - Fu, Li; Wu, Mengyao; Zheng, Yuhong; Zhang, Pengchong; Ye, Chen; Zhang, Huaiwei; Wang, Keqin; Su, Weitao; Chen, Fei; Yu, Jinhong; Yu, Aimin; Cai, Wen; et al. (Sensors and actuators. B, Chemical, 2019)
[Display omitted] •Electrochemical profile of plant tissue shows a unique fingerprint related to the phylogenetic position of plant species.•Introduction of graphene can enhance electrochemical fingerprint signals.•The species within genera can be identified by several patterns and color recognition modes.•Seventeen species of Lycoris were successfully identified with phylogenetic discussion.•This methodology could be further extended for medicinal plant identification as well as to food quality control. The electrochemical activity profile of plant tissue shows a unique fingerprint related to the phylogenetic position of plant species. The assistance of graphene in plant extract adsorption and plant tissue embedding distinctly enhances signal sensitivity using a chip-based portable electrochemical fingerprint recording process. We converted fingerprints recorded under different conditions to recognizable patterns and colours for reliable plant identification. The type and content of electroactive compounds in plants are controlled by genes, so the degree of their differences can be used to reflect genetic differences and subsequently used for studying taxonomic relationships. We then proposed an electro-chemotaxonomical methodology based on multiple fingerprints. Pollens of 17 Lycoris species have been used as a model subject for electro-chemotaxonomical investigation of their infrageneric relationships, and the results have been compared with those of palynological studies. The results are more persuasive than those of classical chemotaxonomic studies and are satisfactorily correlated with taxonomic levels. Due to the extremely low-cost and fast analysis process compared with modern molecular-based taxonomic methods, we believe this technology could play a great role as an assistive technology in the future of phylogenetic studies.